METTL3 potentiates resistance to cisplatin through m6A modification of TFAP2C in seminoma. Issue 19 (28th August 2020) - Wei, Jingchao; Yin, Yinghao; Zhou, Jun; Chen, Hanfei; Peng, Jingxuan; Yang, Jianfu; Tang, Yuxin
Abstract: Testicular germ cell tumours (TGCTs) rank as the most common malignancy in men aged 20‐34 years, and seminomas are the most type of TGCTs. As a crucial anti‐tumour agent with explicit toxicity, cisplatin may render resistance through intertwined mechanisms, even in disease entities with high curative ratio, such as seminoma. Previously, we established cisplatin‐resistant seminoma TCam‐2 (TCam‐2/CDDP) cells and showed that epigenetic regulations, such as non‐coding RNA (ncRNA) interactions, might orchestrate cell fate decisions in the cisplatin treatment context in seminoma. N6‐methyladenosine (m6A) is the most prevalent internal modification in mRNA. In the present study, we assessed cisplatin resistance in seminoma from the perspective of m 6 A, another manner of epigenetic modification. The global m 6 A enrichment of TCam‐2 and TCam‐2/CDDP was depicted. Then, we elucidated whether transcription factor‐activating enhancer‐binding protein 2C (TFAP2C) was functionally m 6 A‐modified by methyltransferase‐like protein 3 (METTL3), which acted as an m 6 A 'writer', and insulin‐like growth factor 2 mRNA‐binding protein 1 (IGF2BP1), which acted as an m 6 A 'reader'. Enhanced stability of TFAP2C mRNA promoted seminoma cell survival under cisplatin treatment burden probably through up‐regulation of DNA repair‐related genes. Hopefully, this study will help improve our understanding of the subtleties of the tumour cellular coping strategy in response to chemotherapy. Targeting factors that are involved in m 6 A methylation may be an effective strategy for circumventing cisplatin resistance in seminoma.